Acinetobacter baumannii, multiresistant to carbapenems at the hospital level. (Revista Torreón Universitario, 2023)
A cross-sectional descriptive study was carried out with the objective of genetically characterizing Acinetobacter baumannii, producer of carbapenemases, 16 strains resistant to carbapenems isolated from patients admitted to the German Nicaraguan public hospital were studied. The identification of the genus, species and the antimicrobial susceptibility test was carried out using the VITEK2 compact system. The synergy test was performed with ethylenediaminetetraacetic acid (10µg or 0.1 uM), from the 0.5 McFarland scale using Kirby Bauer. Genotypic characterization, multiplex PCR was performed for blaOXA23, blaOXA40, blaOXA51 and blaOXA58, also for class B genes, blaIMP, blaVIM, blaGIM, blaSIM, blaSPM and a PCR was performed for blaNDM. As a result of the study, the diversity of genes was demonstrated, 100% of the strains carried OXA51, 87.5% carried OXA40 genes, combined with OXA51, 13% presented a combination of NDM genes with OXA51, 6% of the strains presented genes VIM, GIM in combination OXA40 and OXA51, all the A. baumannii strains under study, presented multiresistance, but 100% were sensitive to colistin. It was concluded that the multiresistance in A. baumannii to carbapenems is due to blaOXA51, an intrinsic gene of this microorganism, and to the combinations of VIM, GIM, NDM and OXA40 genes, increasing the hydrolytic capacity to these antibiotics, these genes are shared by means of plasmids facilitating the vertical and horizontal transfer.
Keywords: Acinetobacter baumannii; Carbapenems; genes; plasmids; Anti-infectives